Genes, personality, and political behavior: A replication and extension using Danish twins. (23rd August 2023) - Weinschenk, Aaron; Dawes, Christopher; Klemmensen, Robert; Rasmussen, Stig Hebbelstrup Rye
Abstract : In this article, we examine whether there is genetic overlap between personality traits and political participation, interest, and efficacy. We make several contributions to the literature. First, we use new data from a large sample of twins from Denmark to examine the link between genes, the Big Five traits, and political behavior. Previous research in this area has not examined the Danish context. Second, because our measures have some overlap with those used in previous studies, we are able to examine whether previous findings replicate in a different sample. Finally, we extend the literature by examining the possible genetic link between some personality and political traits that have not yet been explored. Overall, we find that genes account for a fairly large share of the correlation between two of the Big Five personality traits (openness and extraversion), political participation, and political interest. Thus, most of the relationship between these personality traits and our measures of political behavior can be accounted for by a common underlying genetic component.